ENFORCEMENT OF JINAYAT LAW FOR NON-MUSLIMS IN ACEH - Mahmuddin Mahmuddin; Mansari Mansari; Khairuddin Khairuddin; Ahmad Fikri Oslami; Mul Irawan (Jurnal Hukum dan Peradilan, 2022)
Law enforcement against non-Muslims who commit violations of jinayat law tends to use the penalties stipulated in the Qanun Hukum Jinayat compared to other criminal statutory provisions. This phenomenon is interesting to study because non-Muslims who commit criminal acts (Jarimah) are given the choice of choosing to use Qanun or other Criminal Law which is regulated outside the Qanun. This study aims to analyze how the enforcement of jinayat law against Jarimah is carried out by non-Muslims, why non-Muslims are more likely to choose jinayat law than the provisions of other criminal laws and regulations outside of the Qanun and which penalties are imposed more dominantly by syar'iyah court judges. The author uses the empirical juridical research method with the aim of describing concrete facts about jinayat law enforcement for non-Muslims. The primary legal materials used are Qanun Hukum Jinayat Qanun Hukum Procedural Jinayat. Secondary legal materials, namely through books, journals and research results. Primary data was obtained through interviews with non-Muslims who had been sentenced according to qanun, judges and Wilayatuh Hisbah (WH). The results showed that enforcement of jinayat law for non-Muslims must first seek approval from the suspect to use qanuns or criminal laws other than qanuns. Then the investigator takes action according to the choice set by the suspect. Non-Muslims tend to choose qanuns due to several factors: first, the punishment is more instantaneous than the KUHP which carries a prison sentence. Second, the people who witnessed the execution of the caning were not all citizens who knew him. The more dominant punishments handed down by judges were ta'zir flogging and actions in the form of revoking their business license.